2013
DOI: 10.1136/neurintsurg-2012-010638
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic comparison of the Penumbra system and commonly available syringes in forced-suction thrombectomy

Abstract: Maximizing static and dynamic pressure when performing FST is achieved by aspirating with a syringe possessing both the largest volume and the largest inlet diameter available. Maximizing aspiration force and flow rate is achieved by using the largest catheter possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…In fact, a 0.018 inch microcatheter that remains in a 5 F or 6 F access catheter occludes it to such a degree that almost no aspiration blood flow can be achieved with the recommended setting of the Penumbra pump (table 1 and figures 3 and 4). 17 In other words, pressure must be 3–4 times greater to achieve the same flow as with the BWT when a microcatheter is kept in a 5 F access catheter (table 1). On the other hand, this means that flow must be tripled or quadrupled in order to achieve the same suction.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a 0.018 inch microcatheter that remains in a 5 F or 6 F access catheter occludes it to such a degree that almost no aspiration blood flow can be achieved with the recommended setting of the Penumbra pump (table 1 and figures 3 and 4). 17 In other words, pressure must be 3–4 times greater to achieve the same flow as with the BWT when a microcatheter is kept in a 5 F access catheter (table 1). On the other hand, this means that flow must be tripled or quadrupled in order to achieve the same suction.…”
Section: Discussionmentioning
confidence: 99%
“…It is this suction force which is most important in direct aspiration thrombectomy, and thus maximizing both the vacuum pressure and the catheter tip area can have a significant impact on the effectiveness of thrombectomy. Others have previously shown differences in aspiration flow rates between different catheters [11,12], which is a function of the catheter radius to the fourth power. In contrast, force is the product of pressure and area, where the area of a circle is a function of the radius squared.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the rate of flow of a fluid through a catheter is governed by Poiseuille's law, which states that flow is a function of radius - to the fourth power, pressure, viscosity, and length. Others have examined the flow rates of various thrombectomy catheters [11,12] and found that indeed the size of the catheter is the greatest determinant of flow. However, in direct aspiration thrombectomy, the catheter tip is purposefully occluded by the clot, and thus flow rate is irrelevant.…”
Section: Introductionmentioning
confidence: 99%
“…The Penumbra pump acting alone provided an adequate pump-down time, rapidly creates and maintains a vacuum (figure 2A–C, dotted line) 6. DC and UC cyclic aspiration are shown in figure 2A,B.…”
Section: Resultsmentioning
confidence: 99%
“…We further hypothesized that, by fatiguing the clot, we could measurably improve aspiration performance compared with the static forces characteristic of current suction thrombectomy techniques 6. Moreover, as failure in fatigue is a function of total load cycles,14 we hypothesized that increased aspiration frequencies would lead to increased treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%